Heat Transfer, Volume 3 2002
DOI: 10.1115/imece2002-33916
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Turbulence-Radiation Interactions in Turbulent Reacting Flows

Abstract: Traditional modeling of radiative transfer in reacting flows has ignored turbulence-radiation interactions (TRI). Radiative fluxes, flux divergences and radiative properties have been based on mean temperature and concentration fields. However, both experimental and theoretical work have suggested that mean radiative quantities may differ significantly from those predictions based on the mean parameters because of their strongly nonlinear dependence on the temperature and concentration fields. The composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…This term contributes to the enhancement of flame absorption leading to a reduction in radiant fraction by about 12% (see Table 2). It should be noted that the conclusions drawn from the previous scenarios are consistent with those reported by Li and Modest [14,15] and by Habibi et al [2]in the case of methane jet diffusion flames. Fig.…”
Section: Influence Of Tri-related Terms On Radiative Outputssupporting
confidence: 88%
See 1 more Smart Citation
“…This term contributes to the enhancement of flame absorption leading to a reduction in radiant fraction by about 12% (see Table 2). It should be noted that the conclusions drawn from the previous scenarios are consistent with those reported by Li and Modest [14,15] and by Habibi et al [2]in the case of methane jet diffusion flames. Fig.…”
Section: Influence Of Tri-related Terms On Radiative Outputssupporting
confidence: 88%
“…The second term, referred to as 'emission TRI', is determined on the basis of local properties only and can be evaluated by using either presumed-pdf approaches [2,6,8e12] or pdf composition methods [3e5, 7,13e16]. Li and Modest [14,15] and Habibi et al [2] isolate and quantify different levels of closure for emission TRI in turbulent methane jet flames and showed that the complete absorption coefficient-Planck function correlation must be considered to obtain a reliable evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the peak temperature dropped ΔT RAD = 130, 131, and 262 K for radiation computed with CR-WSGG, NCR-WSGG and gray-gas, respectively. In similar investigation, Li and Modest [36] found a decrease of ΔT RAD = 145 K for a flame with an optical thickness of 0.474. The flame of the current study has an optical thickness of about 0.43, therefore with a slightly smaller influence of thermal radiation, so the differences between the studies are consistent when CR-and NCRWSGGs were employed.…”
Section: Resultsmentioning
confidence: 79%
“…These two TRI correlations were found to be the most important in reactive flows [35][36][37]. Decomposition of temperature and absorption coefficient into average and fluctuating components, T =T + T ′ and κ =κ + κ ′ , followed by time averaging, and neglecting higher order terms, κT 4 can be written as [19]:…”
Section: Turbulence-radiation Interactionsmentioning
confidence: 98%
“…, if the mean free path for radiation is much larger than turbulence integral length scale; this assumption was adopted here and in many other studies dealing with TRI based on the timeaveraged form of the RTE [23,27,28]. Additionally, in the present study it was applied the approximation proposed in [23] and [7], in which both absorption coefficient-temperature correlation and temperature self-correlation are considered.…”
Section: Mathematical Formulationmentioning
confidence: 99%